Influence of kolaviron and vitamin E on ethylene glycol monoethyl ether-induced haematotoxicity and renal apoptosis in rats (2013)
The present study investigated the protective effects of kolaviron, a biflavonoid from the seed of Garcinia kola, and vitamin E on ethylene glycol monoethyl ether (EGEE)-induced haematotoxicity and renal apoptosis in male rats. EGEE was administered at a dose of 200 mg kg_1 alone or simultaneously administered with kolaviron (100 and 200 mg kg_1) and vitamin E (50 mg kg_1) for 14 days. Results of haematological examination showed that white blood cells, platelets, neutrophils and mean corpuscular haemoglobin concentration were significantly lower, whereas lymphocytes were increased in EGEE-exposed rats compared with those in the control. Administration of EGEE caused a significant decrease in the superoxide dismutase and catalase activities as well as in the glutathione level but significantly increased glutathione S-transferase activity and levels of hydrogen peroxide and lipid peroxidation in kidneys of rats compared with those in the control. Also, EGEE-treated rats showed significant elevation in the serum urea and creatinine with marked increase in the frequency of terminal deoxynucleotidyl transferase-mediated dUTP nick end labelling assay-positive apoptotic cells in the tubular epithelial cells in comparison with the control. Co-administration with kolaviron or vitamin E exhibited chemoprotective effects against EGEE-mediated haematotoxicity, augmented renal antioxidant status and prevented the induction of renal apoptosis.